2019
DOI: 10.25082/adep.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement invariance of maternal ratings of ADHD symptoms across clinic referred children’s with and without ADHD

Abstract: The study examined the measurement invariance (configural, metric, scalar, and error variances) and factor mean scores equivalencies of a modified version of the Strengths and Weaknesses of ADHD-Symptoms and Normal Behavior Scale (SWAN-M) across ratings provided by mothers of clinic-referred children and adolescents, diagnosed with (N = 666) and without (N = 202) ADHD. Confirmatory factor analysis (CFA) of these ratings provided support for the bi-factor model of ADHD [orthogonal general and specific factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…These findings converge with the results of previous studies exploring the structure of ADHD symptoms in different age groups and across different measures ( 40 , 52 , 68 ) and are in line with the findings of the single study on the SWAN self-report ( 38 ). On the other hand, diverging interpretations of similar findings have been formulated by different researchers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings converge with the results of previous studies exploring the structure of ADHD symptoms in different age groups and across different measures ( 40 , 52 , 68 ) and are in line with the findings of the single study on the SWAN self-report ( 38 ). On the other hand, diverging interpretations of similar findings have been formulated by different researchers.…”
Section: Discussionsupporting
confidence: 91%
“…In studies on the parent- and teacher-report versions, exploratory factor analysis resulted in a two-factor structure (inattention and hyperactivity/impulsivity) in different samples ( 20 , 31 ). In studies using confirmatory factor analysis ( 31 , 35 , 51 , 52 ), bifactor models were reported to have a better fit than non-hierarchical models; however, similar to studies with other measures, the results suggested a strong and reliable general ADHD factor but mostly weak or unreliable specific factors. A single study under peer review ( 38 ) reported similar results for the new self-report version of the SWAN.…”
Section: Introductionmentioning
confidence: 69%
“…Psychometric properties are comparable between clinically-referred children with and without an ADHD diagnosis. 89 The Toronto Obsessive Compulsive Scale (TOCS) 90 is a 21-item measure of obsessive-compulsive symptoms on a 7-point Likert scale (3=far more than average; −3=far less than average). It has both self-report and parent-report versions with higher scores indicating higher reports of OCD symptoms.…”
Section: Open Accessmentioning
confidence: 99%
“…; Morin et al, 2016). This is called measurement invariance and has been addressed for the SWAN, with the bifactor model, showing invariance over time (Gomez et al, 2020; Gomez, Vance, & Stavropoulos, 2018), age (Normand et al, 2012), and clinical status (Gomez et al, 2019).…”
mentioning
confidence: 99%